2009
DOI: 10.1016/j.actamat.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Healing behavior of preexisting hydrogen micropores in aluminum alloys during plastic deformation

Abstract: Synchrotron X-ray microtomography was used to observe the shrinkage and annihilation behaviors of hydrogen micropores in three dimensions during hot and cold plastic deformation of an Al-Mg alloy. It was examined, by exposing the material to a high temperature after plastic deformation, whether complete healing of micropores is achieved after plastic deformation. Although micropores generally show a pattern of shrinking and closing, closer inspection of a single specimen revealed a variety of geometrically var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 15 publications
2
56
1
Order By: Relevance
“…Actually it has been reported by the present authors with respect to a similar local strain distribution during uniform 60% compression that although a macroscopic applied load is compressive, some regions are locally exposed to tension and even in the compressive regions, compressive strain varies between 0 $ 130%. 9) Wide variation in the morphologically variable behaviors of micro pores during the compression has also been attributed to the observed significant scattering in local strain. …”
Section: Mechanical Requirement For Micro Pore Closurementioning
confidence: 99%
See 3 more Smart Citations
“…Actually it has been reported by the present authors with respect to a similar local strain distribution during uniform 60% compression that although a macroscopic applied load is compressive, some regions are locally exposed to tension and even in the compressive regions, compressive strain varies between 0 $ 130%. 9) Wide variation in the morphologically variable behaviors of micro pores during the compression has also been attributed to the observed significant scattering in local strain. …”
Section: Mechanical Requirement For Micro Pore Closurementioning
confidence: 99%
“…Subsequently, an additional heat treatment was employed at 813 K for 14.4 ks and the specimen was scanned again. Since our previous paper reported that if micro pores are not sufficiently healed, heat treatment causes them to grow again, 9) the additional heat treatment was used to confirm that the micro pores were completely healed. Even if the micro pore size is smaller than the finite spatial resolution of an imaging setup, micro pore closure can be confirmed with this additional heat treatment without failure.…”
Section: Sample and Its Surface Cold Workingmentioning
confidence: 99%
See 2 more Smart Citations
“…The vacancy/ hydrogen pairs was deduced to migrate sufficient distance to be released from the inside of the specimen at much lower temperature than the 3rd peak temperature. Furthermore, Toda et al 24,32) have elucidated presence of hydrogen micropores in pure aluminum and its alloys processed through casting as well as hot and cold rolling. It was pointed out for Al-Mg alloys that micropores filled and pressurized with molecular hydrogen are predominant hydrogen trap site, while the occupancy for dislocation traps is very high both in the alloys and pure aluminum.…”
Section: Resultsmentioning
confidence: 99%